Sams teach yourself Movable Type in 24 hours - Holzschlag, Molly E. (Sams, 2004)
Movable Type, a low-cost, distributed publishing software solution is helping thousands of Web site developers organize and automate the Web content management process. In 24 well-paced chapters, the authors of Sams Teach Yourself Movable Type in 24 Hours show readers how to install, personalize, and configure Movable Type into an indispensable content management tool. Features hands-on tutorials for finding Web hosting services, adjusting publishing preferences, customizing page templates, setting up multiple author accounts and extending the program with plug-ins and custom features, the authors show readers how to use everything from the most basic fundamentals of Movable Type to its most powerful features.